The effect of acute traumatic brain injury on cardiovascular homeostasis - McMahon, Christine Geraldine (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Medical Gerontology, 2008)
Acute traumatic brain injury (TBI) remains the most common cause of death from multiple trauma. The cardiovascular homeostatic responses to haemorrhage and injury are co-coordinated in the central nervous system. Coincidental brain injury, which is present in at least 21% of trauma patients, could impair these responses and thereby adversely affect outcome. The effects of acute TBI on cardiovascular homeostatic mechanisms are unclear. The first objective of this research was to test the hypothesis that acute TBI of moderate severity (Abbreviated Injury Score=3) impairs survival from multiple trauma. Analysis of the UK trauma audit and research network database was undertaken in a study population of multiple trauma patients who had sustained blunt trauma with an injury severity score (ISS) ranging between 16 and 50. These parameters were chosen to reflect an injury severity where acute TBI could affect mortality. The probability of death was modeled using logistic regression adjusted for age and injury severity. Moderate TBI in isolation was associated with a low mortality rate (< 4.7%). Adjusting for ISS, mortality from multiple trauma was doubled in the presence of moderate TBI (odds ratio 2.08, 95% Cl, 1.57-2.77). This observation led to the hypothesis that acute TBI could modify cardiovascular homeostasis, and thereby contribute to the additional mortality observed when TBI and extracranial injuries are combined.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin